Strengthening Financial Systems in Developing Countries : The Case for Incentives-Based Financial Sector Reforms - Bossone, Biagio (World Bank, Washington, DC, 2017)
An international cooperative effort has been focused on the need to reduce financial fragility and systemic risks in global financial markets. Work is proceeding in three different areas: enhancing financial market transparency, improving the international financial architecture, and strengthening financial systems. Strengthening financial systems (the focus of this paper) means cooperating to promote principles and sound practices for financial stability through development of well-functioning financial systems and market discipline. Financial sector reform and development is much more than setting rules, articulating standards, approving legislation, and creating new institutions. All are important but ultimately behavior must be changed if there is to be meaningful and lasting financial reform. For that reason, this paper emphasizes the role of incentives to induce appropriate behavior. Developing countries have made important progress toward improved financial supervision in the past few years. Reforming financial sectors is a lengthy and complex process of institution building and incentive reorientation, whose success requires full ownership of, and participation in, the process by society and its government.